2012
DOI: 10.1016/j.biomaterials.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inflammation in a mouse model of rheumatoid arthritis using targeted lipase-labile fumagillin prodrug nanoparticles

Abstract: Nanoparticle-based therapeutics are emerging technologies that have the potential to greatly impact the treatment of many human diseases. However, drug instability and premature release from the nanoparticles during circulation currently preclude clinical translation. Herein, we use a lipase-labile (Sn 2) fumagillin prodrug platform coupled with a unique lipid surface-to-surface targeted delivery mechanism, termed contact-facilitated drug delivery, to counter the premature drug release and overcome the inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…The passive targeting of nanomedicines to inflamed tissues based on enhanced permeability has been supported by various in vivo biodistribution studies [51,56,59,63,70]. Ishihara et al showed that PEGylated polymersomes encapsulated with the glucocorticoid betamethasone preferentially accumulated in inflamed joints in a mouse model of antibody-induced arthritis.…”
Section: Current Landscape Of Nanomedicine For Ramentioning
confidence: 99%
See 2 more Smart Citations
“…The passive targeting of nanomedicines to inflamed tissues based on enhanced permeability has been supported by various in vivo biodistribution studies [51,56,59,63,70]. Ishihara et al showed that PEGylated polymersomes encapsulated with the glucocorticoid betamethasone preferentially accumulated in inflamed joints in a mouse model of antibody-induced arthritis.…”
Section: Current Landscape Of Nanomedicine For Ramentioning
confidence: 99%
“…This increased localization was interesting, as the conjugated liposomes were cleared significantly faster from circulation than the nonconjugated liposomes, showing how effective the targeted liposomes were, even with a shorter circulation time [59]. The same receptor was also targeted for the delivery of an angiogenesis inhibitor, fumagillin and the targeted fumagillin showed a higher affinity to inflamed tissues, decreased leukocytes recruited into the tissues, and suppressed inflammation [70]. In addition, the effective dose of the optimized targeted fumagillin nanoparticle formulation was decreased by eightfold [70].…”
Section: Current Landscape Of Nanomedicine For Ramentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, delivery of lipase-labile fumagillin prodrug (Fum-PD) was achieved using perfluorocarbon targeted with αvβ3-integrin peptidomimetic antagonists. 93,94 Fum-PD nanotherapy induces the production of endothelial nitric oxide by which it indirectly suppresses inflammation in experimental RA. Tocilizumab-loaded hyaluronate-gold nanoparticles targeted with a monoclonal antibody against IL-6 have also been tested in CIA mice.…”
Section: Targeted Np Approach In Ramentioning
confidence: 99%
“…22), that transfers nanoparticle (NP) lipid surfactant components to the targeted cell membrane through a hemifusion complexation process (23). Moreover, we have advanced this technology through the recent development of phospholipid Sn 2 prodrugs that stabilize and sequester the drug in the hydrophobic aspect of the outer lipid membrane of nanocolloids and prevent premature drug escape or metabolism during circulation to target cells (24, 25). Following transfer of the lipid monolayer components to the target cell membrane, cytosolic lipases enzymatically cleave the Sn 2 ester and liberate the drug into the cytosol (25, 26).…”
Section: Introductionmentioning
confidence: 99%